The origins of the full-field flash electroretinogram b-wave - Bhatt, Yashvi; Hunt, David M.; Carvalho, Livia S. (Frontiers in Molecular Neuroscience, 2023)
The electroretinogram (ERG) measures the electrical activity of retinal neurons and glial cells in response to a light stimulus. Amongst other techniques, clinicians utilize the ERG to diagnose various eye diseases, including inherited conditions such as cone-rod dystrophy, rod-cone dystrophy, retinitis pigmentosa and Usher syndrome, and to assess overall retinal health. An ERG measures the scotopic and photopic systems separately and mainly consists of an a-wave and a b-wave. The other major components of the dark-adapted ERG response include the oscillatory potentials, c-wave, and d-wave. The dark-adapted a-wave is the initial corneal negative wave that arises from the outer segments of the rod and cone photoreceptors hyperpolarizing in response to a light stimulus. This is followed by the slower, positive, and prolonged b-wave, whose origins remain elusive. Despite a large body of work, there remains controversy around the mechanisms involved in the generation of the b-wave. Several hypotheses attribute the origins of the b-wave to bipolar or Müller glial cells or a dual contribution from both cell types. This review will discuss the current hypothesis for the cellular origins of the dark-adapted ERG, with a focus on the b-wave.